If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + -3(a + 1) = 6 + -5a Reorder the terms: 7a + -3(1 + a) = 6 + -5a 7a + (1 * -3 + a * -3) = 6 + -5a 7a + (-3 + -3a) = 6 + -5a Reorder the terms: -3 + 7a + -3a = 6 + -5a Combine like terms: 7a + -3a = 4a -3 + 4a = 6 + -5a Solving -3 + 4a = 6 + -5a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '5a' to each side of the equation. -3 + 4a + 5a = 6 + -5a + 5a Combine like terms: 4a + 5a = 9a -3 + 9a = 6 + -5a + 5a Combine like terms: -5a + 5a = 0 -3 + 9a = 6 + 0 -3 + 9a = 6 Add '3' to each side of the equation. -3 + 3 + 9a = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 9a = 6 + 3 9a = 6 + 3 Combine like terms: 6 + 3 = 9 9a = 9 Divide each side by '9'. a = 1 Simplifying a = 1
| 1.8+9=-5.7-6 | | 5(3e+5)-25e= | | t^2+9t=18 | | v+31=-3(1-6v) | | 13*4x+2x=1x*6-12 | | 9x*9x+5=41 | | -33+4k=-2(k-4)-5 | | 13*4x+2x= | | 6x^2-5x-1=3 | | -20+8r=4(-5-6r) | | X+Y=140 | | c/5-4=-3 | | 4(2n+5)+2n=36+8n | | 0=9-x^2 | | 81+5=41 | | -9+6x=4-5(x-4) | | 2x-(9x-4)= | | 6x-(3x+5)=22 | | -6(p+5)=-16-8p | | 2+8x=20-x | | -8k+ra=r-2y | | -8k+ar=r-2y | | 4/6=m/9 | | -18=6(6x+3)+4(x-9) | | 3r-4r+1r=-12 | | .666.....x+5=.666...+14 | | -3(3-8k)=-8k+23 | | -2y^2+3y+5= | | -(3x+7)=-8-4x | | 14+14= | | AB+CD=E | | .3333.....x+5=.333...+14 |